The incidence of injury in surfboat rowers - Moseley, L. (Australian Journal of Science and Medicine in Sport, 1997)
A questionnaire was completed by 202 surfboat rowers. The questionnaire investigated injuries that occurred over the preceding two years. The injuries were classified according to the nature of onset of the injury, the anatomical location of the injury, and the age of the rower. Eighty percent of surfboat rowers reported some type of injury during the two years prior to completing the questionnaire. Eighty one percent of injuries were classified as chronic insidious onset injuries. The mean time lost from employment due to chronic insidious onset injuries was 10.4 days, Low back pain accounted for 60% of all injuries. Sixty percent of the acute injuries were hamstring or calf tears that were incurred during sprint running training. No relationship between age or surfboat rowing experience and incidence of injury was identified. The present study suggests that there is a high incidence of injury in surfboat rowing, and that most injuries are chronic injuries and are of an insidious onset.